Ustekinumab is associated with superior effectiveness outcomes compared to vedolizumab in Crohn's disease patients with prior failure to anti‐TNF treatment. Issue 1 (22nd May 2020) - Biemans, Vince B. C.; van der Woude, C. Janneke; Dijkstra, Gerard; van der Meulen‐de Jong, Andrea E.; Löwenberg, Mark; de Boer, Nanne K.; Oldenburg, Bas; Srivastava, Nidhi; Jansen, Jeroen M.; Bodelier, Alexander G. L.; West, Rachel L.; de Vries, Annemarie C.; et al.
Summary: Background: Both vedolizumab and ustekinumab can be considered for the treatment of Crohn's disease (CD) when anti‐TNF treatment fails. However, head‐to‐head trials are currently not available or planned. Aim: To compare vedolizumab and ustekinumab in Crohn´s disease patients in a prospective registry specifically developed for comparative studies with correction for confounders. Methods: Crohn´s disease patients, who failed anti‐TNF treatment and started vedolizumab or ustekinumab in standard care as second‐line biological, were identified in the observational prospective Dutch Initiative on Crohn and Colitis Registry. Corticosteroid‐free clinical remission (Harvey Bradshaw Index ≤4), biochemical remission (C‐reactive protein ≤5 mg/L and fecal calprotectin ≤250 µg/g), combined corticosteroid‐free clinical and biochemical remission, and safety outcomes were compared after 52 weeks of treatment. To adjust for confounding and selection bias, we used multiple logistic regression and propensity score matching. Results: In total, 128 vedolizumab‐ and 85 ustekinumab‐treated patients fulfilled the inclusion criteria. After adjusting for confounders, ustekinumab‐treated patients were more likely to achieve corticosteroid‐free clinical remission (odds ratio [OR]: 2.58, 95% CI: 1.36‐4.90, P  = 0.004), biochemical remission (OR: 2.34, 95% CI: 1.10‐4.96, P  = 0.027), and combined corticosteroid‐free clinical and biochemical remission (OR: 2.74, 95% CI: 1.23‐6.09, P  = 0.014), while safety outcomes (infections: OR: 1.26, 95% CI: 0.63‐2.54, P  = 0.517; adverse events: OR: 1.33, 95% CI: 0.62‐2.81, P  = 0.464; hospitalisations: OR: 0.67, 95% CI: 0.32‐1.39, P  = 0.282) were comparable between the two groups. The propensity score matched cohort with sensitivity analyses showed comparable results. Conclusions: Ustekinumab was associated with superior effectiveness outcomes when compared to vedolizumab, while safety outcomes were comparable after 52 weeks of treatment in CD patients who have failed anti‐TNF treatment.